Mapania meekiongii, a new species of Mapania (Cyperaceae) from Sarawak, Malaysia - Miraadila, M.I.; Shabdin, Z. (Folia malaysiana, 2016)
Mapania meekiongii Miraadila & Shabdin, a new species from Sarawak is described and illustrated. The appearance of Mapania meekiongii is reminiscent of both M. cuspidata and m. sapuniana but differs by some other morphological characters.